2013
DOI: 10.1302/0301-620x.95b1.30908
|View full text |Cite
|
Sign up to set email alerts
|

Litigation after hip and knee replacement in the National Health Service

Abstract: The results of hip and knee replacement surgery are generally regarded as positive for patients. Nonetheless, they are both major operations and have recognised complications. We present a review of relevant claims made to the National Health Service Litigation Authority. Between 1995 and 2010 there were 1001 claims to a value of £41.5 million following hip replacement surgery and 523 claims to a value of £21 million for knee replacement. The most common complaint after hip surgery was related to residual neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 6 publications
2
50
2
1
Order By: Relevance
“…[23][24][25][26] A recent review has identified that smaller females are more likely to be susceptible to leg length changes. 20 The reason for this is that a given magnitude of inequality will cause a corresponding change in angle of the pelvis with respect to the sagittal plane. The magnitude of this pelvic angle is inversely proportional to the width of the pelvis, making smaller people more likely to be symptomatic.…”
Section: (2)effect Of Total Hip Replacement Surgerymentioning
confidence: 99%
“…[23][24][25][26] A recent review has identified that smaller females are more likely to be susceptible to leg length changes. 20 The reason for this is that a given magnitude of inequality will cause a corresponding change in angle of the pelvis with respect to the sagittal plane. The magnitude of this pelvic angle is inversely proportional to the width of the pelvis, making smaller people more likely to be symptomatic.…”
Section: (2)effect Of Total Hip Replacement Surgerymentioning
confidence: 99%
“…The mean preoperative and postoperative leg length discrepancies were -5.8 ± 6.3 and 0.7 ± 3.5 mm, respectively. Three patients had lengthening of the postoperative legs by >5 mm (7,8, and 9 mm), but none had > 10-mm lengthening in comparison to the non-operative side. The results of this research show minimal postoperative leg length discrepancy and global offset, with values of 0.7 ± 3.5 and 0.7 ± 6 mm, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…One of the major complications after THA is leg length discrepancy, which can sometimes result in litigation [8]. Sykes et al [9] reported that for discrepancies ≥ 5 mm, a significant number of participants were aware of the difference.…”
Section: Discussionmentioning
confidence: 99%
“…According to the claims presented to the British NHS Litigation Authority in the period 1995-2010, one of the most common complaints after TKA is for Infection [ 6 ]. The actual direct costs of periprosthetic and other bone and joint infections need thorough evaluation as they are responsible for substantial fi nancial losses in the hospital budgets due to inadequate re-imbursement.…”
mentioning
confidence: 99%